2004
DOI: 10.1038/sj.bjc.6601737
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic features of upper gastrointestinal tract cancers in Northeastern Iran

Abstract: Previous studies have shown that oesophageal and gastric cancers are the most common causes of cancer death in the Golestan Province, Iran. In 2001, we established Atrak Clinic, a referral clinic for gastrointestinal (GI) diseases in Gonbad, the major city of eastern Golestan, which has permitted, for the first time in this region, endoscopic localisation and histologic examination of upper GI cancers. Among the initial 682 patients seen at Atrak Clinic, 370 were confirmed histologically to have cancer, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 21 publications
9
117
2
1
Order By: Relevance
“…These two exposures are major risk factors for oesophageal squamous cell carcinoma in Western populations (Brown et al, 1994(Brown et al, , 2001), but play a much smaller role in such high-risk areas, such as Linxian (Tran et al, 2005) or northeastern Iran (Cook-Mozaffari et al, 1979;Islami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These two exposures are major risk factors for oesophageal squamous cell carcinoma in Western populations (Brown et al, 1994(Brown et al, , 2001), but play a much smaller role in such high-risk areas, such as Linxian (Tran et al, 2005) or northeastern Iran (Cook-Mozaffari et al, 1979;Islami et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…With above statement, we can explain a predominance of cardiac cancer compared to all types of gastric cancers because it is more symptomatic (Islami et al, 2004;Kumar, 2007).…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gasmentioning
confidence: 95%
“…One important suggestion that need to be considered in morphological and topographic changes would be error due to investigation criteria. For example, study from Golestan province on 1969-71 (Islami et al, 2004) showed the ratio of esophageal /gastric cancer was estimated about 8/1 but in another study on 2001 (Islami et al, 2004) it was estimated about 2/1. This notable change might be result of changing in the technique of diagnosis because endoscopy had not been used in the older study and it's possible to diagnose many of cardiac tumors as esophageal cancer (due to dysphagia) (Islami et al, 2004).…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gasmentioning
confidence: 99%
“…Etiologic factors responsible for these high rates are largely unknown (Islami et al, 2004), and only two studies have examined the role of diet in association with oesophageal cancer in this area (Hormozdiari et al, 1975;Cook-Mozaffari et al, 1979). Residents in the high incidence areas had lower intake of vitamins A and C, riboflavin, animal proteins and fresh vegetables and fruits and a higher consumption of sheep and goat milk than that of residents in other areas (Hormozdiari et al, 1975).…”
Section: Introductionmentioning
confidence: 99%